Electron capture dissociation of extremely supercharged protein ions formed by electrospray ionisation1. Issue 17 (7th September 2015) - Zenaidee, Muhammad A.; Donald, William A.
<x xml:space="preserve">Abstract</x> Extreme supercharging of proteins yields significant performance gains for the direct characterization of protein sequences by electron capture dissociation mass spectrometry.